2016
DOI: 10.1007/s10896-016-9797-z
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment in College Women: Effect on Severe Physical Partner Violence

Abstract: This study examined risk of severe physical partner violence victimization as a function of childhood maltreatment among college women. Engaged and soon to be engaged female students were recruited for the study. Compared to their counterparts, risk of severe physical partner violence was three-fold greater in women who experienced childhood physical violence and five-fold greater among those who witnessed mother-to-father violence. Victims of childhood maltreatment may encounter social and personal problems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
3
13
0
1
Order By: Relevance
“… 42 45 Further in a study by Al-Modallal, which examined the risk of partner physical violence victimisation as a function of childhood maltreatment among college women in Jordan, the findings revealed that the risk of severe physical partner violence was three times greater among women who had experienced childhood physical violence and five times greater among those who had witnessed father-to-mother violence. 44 The review confirms the theoretical model which hypothesises about the relationship between the children’s exposure to violence and the risk for IPV. The likelihood of experiencing IPV among women who have ever been exposed to violence in childhood might be through the mechanism of their lacking in coping skills.…”
Section: Discussionsupporting
confidence: 70%
“… 42 45 Further in a study by Al-Modallal, which examined the risk of partner physical violence victimisation as a function of childhood maltreatment among college women in Jordan, the findings revealed that the risk of severe physical partner violence was three times greater among women who had experienced childhood physical violence and five times greater among those who had witnessed father-to-mother violence. 44 The review confirms the theoretical model which hypothesises about the relationship between the children’s exposure to violence and the risk for IPV. The likelihood of experiencing IPV among women who have ever been exposed to violence in childhood might be through the mechanism of their lacking in coping skills.…”
Section: Discussionsupporting
confidence: 70%
“…The continuing practice of IPV in families and communities affects the socialization of young people [12][13][14]. In addition and of major concern, is that young people start dating early in their lives [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the victims are mainly females knowing that females are more vulnerable to certain types of abuse compared to males (Brown et al, 2005). Third, having a history of childhood abuse increases a woman’s likelihood of adult victimization (Al-Modallal, 2016a; Hetzel & McCanne, 2005; Woods et al, 2005). This happens because women will be, at some point, under the control of a male partner who may practice abuse against them.…”
mentioning
confidence: 99%
“…In a cross-sectional study among women admitted to psychiatric services in one county in the south of Sweden, investigators revealed that 51% of the participants reported the experience of abuse in their childhood (Nilsson et al, 2005). The victimization rate was lower in a Jordanian sample where 26.7% of the participating women reported experiences of child abuse (Al-Modallal, 2016a).…”
mentioning
confidence: 99%
See 1 more Smart Citation